Crecimiento de plántulas de Campsiandra angustifolia "huacapurana" utilizando diferentes dosis de NPK, CIEFOR - Puerto Almendra, Loreto - Perú, 2021 - Arista Oversluijs, Adriana Gabriela (2022)
The study was carried out in Parcel No. 12 in Ciefor - Puerto Almendras, evaluating 200 Campsiandra angustifolia plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by treatment B (20% NPK dose) with a value of 0,58 mm between the first and last evaluation. There is a difference between the averages of the increase in diameter of the plants, where treatment E (80% of NPK dose) presents the highest average with 86,89 mm. The greatest increase in height was presented by treatment B with a value of 45,28 cm. The results of the nonparametric Kruskal Wallis test for the comparison of height increase and the treatments indicate that there is a difference between the averages, the treatment B showing the highest value with 93,27 cm. A total of 149 live Campsiandra angustifolia "huacapurana" plants were found, representing 83.5% of the total; while it had a mortality of 33 plants (16.5%). At a general level in the experiment, the Bueno quality (Treatment B, C, D and E) was recorded for the Campsiandra angustifolia seedlings at the end of the study.